Cooking with the Community: Addressing Food Insecurity Through Equipment Provision and Professional Instruction - Ryan L. Spotts, MD; Brittany A. Massare, MD; Madeline Matzelle-Zywicki, BS; Ashley Sun, BA; Lisa R. Yoder, BS; Eric W. Schaefer, MS; Angela L. Zearfaus, MD; Deepa L. Sekhar, MD (Elsevier, 2024)
Introduction: Food insecurity is a common problem with many associated negative downstream health impacts. Despite government sponsored and private supports, many individuals struggle with making healthy, nutritious meals. Penn State's Cooking with the Community program was constructed with the objective of providing cooking equipment and instructions to increase knowledge of healthy cooking techniques and consumption of under-utilized food pantry ingredients. Methods: Four cooking demonstrations were held over an 8-month study period in 2021 designed to educate participants on under-utilized and seasonally available ingredients. Each demonstration was professionally led by a chef who taught cooking skills and the use of different equipment, which were subsequently gifted to the participants. Participants were surveyed before and after each demonstration to assess cooking perceptions and comfort using Likert scales. Final analysis was completed in 2022 using mixed effects models to analyze changes between pre- and post-demonstration. Results: There were 34 total participants. Statistically significant improvements were seen in confidence in cooking (mean increase=0.5; SD=0.2; p=0.031; 95% CI=0.1, 1.0), preparation of a simple recipe (mean increase=0.6; SD=0.2; p=0.013; 95% CI=0.1, 1.0), and cooking new foods (mean increase=0.6; SD=0.3; p=0.026; 95% CI=0.1, 1.1). Conclusions: Cooking with the Community provides valuable information on how cooking confidence may be boosted within vulnerable populations by providing cooking equipment and professional instructions on its use.